2012
DOI: 10.3116/16091833/13/4/170/2012
|View full text |Cite
|
Sign up to set email alerts
|

Appearance of optical singularities at the light propagation through glasses with residual stresses

Abstract: Abstract. We have shown that residual stresses existing in isotropic glass media lead to appearance of polarisation singularities of optical wave front. These singularities are characterised by the strength of topological defect equal to 1/ 2  and should lead to the appearance of optical vortices with the topological charge 1  . Annealing of the samples has led to annihilation of the polarisation singularities, homogenisation of spatial distribution of the phase difference and zeroing of the latter, thus sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…torsion or bending of material rods, whenever the dislocations of crystalline structures are available [10,11]. Moreover, the TDs of OI orientation can appear in transparent glasses characterized by residual mechanical stresses [12]. It is interesting that similar TDs have been detected in the work [13].…”
Section: Introductionmentioning
confidence: 87%
“…torsion or bending of material rods, whenever the dislocations of crystalline structures are available [10,11]. Moreover, the TDs of OI orientation can appear in transparent glasses characterized by residual mechanical stresses [12]. It is interesting that similar TDs have been detected in the work [13].…”
Section: Introductionmentioning
confidence: 87%
“…For example, optical polarization singularities are successfully created using torsion of crystals, their bending [9][10][11], or loading of transparent crystalline disks compressed along their diameters [12]. It has also been found that optical polarization singularities are imposed by structural dislocations existing in crystals or by residual stresses available in glass materials [13]. Moreover, singularities with the strength of topological defects equal to ½ can be induced by conically shaped electric field via the Pockels effect [14].…”
Section: Introductionmentioning
confidence: 99%